Pressure dependence of room-temperature structural properties of CaAl2Si2. (17th June 2020) - Strikos, S; Joseph, B; Alabarse, F G; Valadares, G; Costa, D G; Capaz, Rodrigo B; ElMassalami, M
Abstract: We investigated the pressure dependence of the crystal structure of CaAl2 Si2 by means of ab initio calculations and room-temperature synchrotron x-ray powder diffraction. Ab initio calculations reproduce satisfactorily the experimentally observed pressure-dependent structural evolution up to 3 GPa where the title system remains in the trigonal P 3 ¯ m 1 phase. In the pressure range 3–8 GPa, pressure evolution of the calculated in-plane lattice parameters is steeper than the observed. Ab initio calculations predict a structural phase transition to a tetragonal phase ( P 3 ¯ m 1 to I4/mmm) near 7.5 GPa for zero (or room) temperature. Temperature effects are included through calculation of vibrational properties (phonon spectra). These calculations confirm that both phases are either globally or locally stable (metastable) and allow for the construction of a P − T phase diagram for this system. However, our experiments show no sign of such a transition up to 12 GPa. Such a discrepancy can be explained if one considers the trigonal ( P 3 ¯ m 1 ) structure to be metastable above the critical pressure, but is separated from the predicted tetragonal (I4/mmm) structure by a relatively high energy barrier. The applied pressure alone may not be able to surpass the energy-barrier; rather a joint high-pressure and high-temperature (HPHT) treatment may lead to it. However, empirical verification of such a hypothetical transition may be hampered by the chemistry of CaAl2 Si2 system which shows tendency to decompose peritectically into Ca2 Al3 Si4 and aluminum under HPHT treatment.